A slurry preparation process for high thermal conductivity silicon nitride slurry

By using a polymer bound to the modified tannin acid and rosin to cooperate with the silicon nitride powder in the preparation process of the highly thermally conductive silicon nitride slurry, the problem of difficult to obtain controllable standard slurry and prone to cracking in the casting process in the prior art is solved, and efficient dispersion and bonding of the slurry is achieved, and flexibility and performance are improved.

CN119114216BActive Publication Date: 2025-03-25江苏富乐华功率半导体研究院有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411255108.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-03-25
Estimated Expiration
2044-09-09

AI Technical Summary

Technical Problem

In the prior art, when preparing high thermal conductivity silicon nitride slurry, it is difficult to obtain controllable standard slurry, and cracking or falling off is prone to occur during casting.

Method used

High thermal conductivity silicon nitride slurry was prepared by mixing the silicon nitride powder with a ball mill medium for dispersion and grinding, and adding organic glue liquid for mixer sol treatment and sol ball milling treatment. In this method, 3-aminopropyltriethoxysilane and lysine are used as small molecule additives, and the modified tannin acid and rosin are combined through chemical bonding to form a polymer, which synergistically acts on the silicon nitride powder to improve its dispersion and adhesion in the slurry.

Benefits of technology

The efficient dispersion and bonding of silicon nitride slurry is achieved, the flexibility and performance of the slurry are improved, cracking or falling off during casting is avoided, and the optimal ball milling state can be confirmed through noise detection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114216B_ABST
    Figure CN119114216B_ABST
Patent Text Reader

Abstract

The invention discloses a slurry making process of high thermal conductivity silicon nitride slurry, which relates to the technical field of slurry. The process comprises the following steps: step 1: mixing silicon nitride powder and ball milling medium, and performing dispersed grinding to obtain slurry powder; step 2: (1) adding the slurry powder into an organic glue to obtain a mixed slurry; (2) subjecting the mixed slurry to a sol treatment in a stirrer to obtain a mixed slurry A; and (3) subjecting the mixed slurry A to a sol ball milling treatment, and filtering through 200 meshes to obtain a high thermal conductivity silicon nitride slurry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of slurry, in particular to a slurry making process of high thermal conductivity silicon nitride slurry. Background Art

[0002] The raw materials are fed into the hollow cylinder through the ball milling port for ball milling. The cylinder is filled with grinding balls (silicon nitride) with a diameter of 5 mm. When the cylinder rotates around the horizontal axis at a certain speed, the medium and raw materials in the cylinder are ejected or rolled down from the inner wall of the cylinder when the gravity is greater than the centrifugal force as the cylinder reaches a certain height. The agglomerated slurry is broken due to the impact force. At the same time, during the rotation of the mill, the sliding movement of the solvent medium between each other also grinds the raw materials, making the slurry particles finer.

[0003] When mass production is put into use, it is necessary to invest more resources to experiment with the parameters of the ball milling process, which is different from the type and size of laboratory equipment. When using conventional processes, the material type / ball mill type / silicon nitride ball ratio can only rely on the experience of the experimenters; investing resources to explore the appropriate process will not produce effective results even if it is repeated many times, and it is impossible to obtain a controllable standard slurry.

[0004] In summary, it is of great significance to prepare a high thermal conductivity silicon nitride slurry. Summary of the invention

[0005] The purpose of the present invention is to provide a method to solve the problems raised in the prior art.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A slurrying process for high thermal conductivity silicon nitride slurry comprises the following steps:

[0008] Step 1: Mix silicon nitride powder and ball milling media, and disperse and grind them to obtain slurry powder;

[0009] Step 2: (1) adding the slurry powder to the organic glue to obtain a mixed slurry; (2) subjecting the mixed slurry to a sol treatment in a blender to obtain a mixed slurry A; (3) subjecting the mixed slurry A to a sol ball mill treatment, filtering through 200 meshes, and obtaining a high thermal conductivity silicon nitride slurry.

[0010] More optimally, during the dispersed grinding process, the ball loading of the ball milling medium is 25% to 45%, the loading of the silicon nitride powder is 30% to 45%; the ball milling speed is 25 r / min to 30 r / min, the ball milling time is 4 to 8 hours; and the noise decibel value during the process is 77 to 78.

[0011] Preferably, the ball milling medium is silicon nitride ball; the particle size of the slurry powder includes 0.1 μm<D10<0.3 μm, 0.5 μm<D50<0.7 μm, and 1.2 μm<D90<1.5 μm.

[0012] More optimally, the sol treatment time of the mixer is 4 to 6 hours; the viscosity of the mixed slurry A at 50° C. is 24000 cp to 25000 cp.

[0013] More optimally, during the sol ball milling process, the ball loading of the ball milling medium is 25% to 45%, and the loading of the mixed slurry is 30% to 45%; the ball milling speed is set based on the noise decibel value in the range of 77 to 78 during the process, and the ball milling time is 6 to 8 hours.

[0014] More optimally, the mixed slurry includes the following raw materials: by weight, 20 to 30 parts of slurry powder and 70 to 80 parts of organic glue; the organic glue includes the following raw materials: by weight, 2 to 3 parts of polymer, 1 to 1.5 parts of additives, and 65 to 72 parts of deionized water.

[0015] More optimally, the auxiliary agent includes 3-aminopropyltriethoxysilane and lysine in a mass ratio of 3 to 3.5:1.5 to 2.

[0016] The preparation method of the polymer is more optimized as follows: (1) adding tannic acid, hydroxy-polyethylene glycol-chloride, chloroethyl acrylate, triethylamine and the like to a reaction system; stirring at 100°C to 110°C for 20 to 30 minutes, dripping 4 to 5 mol / L NaOH aqueous solution for 15 to 20 minutes; reacting for 4 to 6 hours, cooling to room temperature, purifying, and drying to obtain modified tannic acid; (2) under nitrogen protection, heating rosin to 120 to 130°C, adding maleic anhydride and peroxide initiator and mixing evenly, then heating to 190 to 200°C, reacting for 3 to 5 hours, adding modified tannic acid, heating to 250 to 280°C, continuing to react for 5 to 7 hours, until the temperature drops to 110 to 125°C, adding antioxidant 1010, mixing evenly, cooling to room temperature, and obtaining a polymer.

[0017] More optimally, the raw materials of the modified tannic acid include the following components: by mass, 1 to 1.5 parts of tannic acid, 0.3 to 0.4 parts of hydroxy-polyethylene glycol-chloride, 0.4 to 0.6 parts of chloroethyl acrylate, 0.1 to 0.3 parts of triethylamine, and 2 to 3 parts of 4 to 5 mol / L NaOH aqueous solution; the raw materials of the polymer include the following components: by mass, 1.5 to 3 parts of rosin, 0.3 to 0.5 parts of maleic anhydride, 0.008 to 0.024 parts of peroxide initiator, 0.2 to 0.24 parts of modified tannic acid, and 0.004 to 0.007 parts of antioxidant 1010.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] In the present invention, 3-aminopropyl triethoxysilane and lysine are used as small molecule additives; polyethylene glycol (PEG) segments and chloroethyl acrylate are introduced into tannic acid, wherein the polyethylene glycol (PEG) segments are beneficial to improving the water solubility of the polymer and the reactivity with other groups; the acrylic acid group is introduced into the modified tannic acid, thereby increasing the functionality and compatibility of the polymer; and then, anhydride bonds are introduced into rosin to react with hydroxyl groups in the modified tannic acid to form stable ester bonds, thereby combining the modified tannic acid and rosin together through chemical bonds to form a polymer. The polymer and the small molecule additives act synergistically, which is beneficial to the dispersion of silicon nitride powder in the slurry, thereby improving the performance of the slurry.

[0020] The silicon nitride slurry itself is relatively hard. If it encounters some irregular surfaces or parts that need to be bent during the casting process, it will crack or fall off. The polymer prepared by the present invention can interact with the surface of silicon nitride particles through its own long-chain molecules and polar groups, and can effectively disperse the silicon nitride particles to prevent the agglomeration of the particles. In addition, the polymer is interspersed between the silicon nitride particles to form a cross-linked network, which enhances the adhesion between the particles and improves the flexibility of the subsequent blank of the slurry. Therefore, after adding the organic glue, the silicon nitride slurry will become flexible.

[0021] When the horizontal ball mill is running, it is impossible to accurately determine the state of the balls falling inside, and it is inconvenient for personnel to adjust and judge the speed of the ball mill. The present invention can confirm the best ball milling state through noise detection. There are two sounds during operation, the sound of the balls sliding down and the sound of the balls falling. The ball falling is the main source of noise. Studies have found that the larger the noise peak and the louder the sound of the balls falling, the more suitable it is for slurry dispersion and grinding. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the noise result diagram corresponding to the ball loading of 40%, material loading of 40%, and ball milling at 25r / min;

[0023] Figure 2This is the noise result diagram corresponding to the ball loading of 40%, material loading of 40%, and ball milling at 30r / min;

[0024] Figure 3 For the particle size test of the sample taken in Example 2, the particle size evaluation graphs were performed without ultrasound and with ultrasound for 2 minutes;

[0025] Figure 4 This is a scraping diagram of the casting machine after adding organic glue in Example 1;

[0026] Figure 5 This is a scraping diagram of the casting machine after adding organic glue in Example 2;

[0027] Figure 6 This is a scraping diagram of the casting machine after adding organic glue in Example 3;

[0028] Figure 7 This is a microscopic observation diagram of Example 2 after staining with gentian violet solution. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] In the following specific implementation methods, parts are by mass. In the present embodiment, it should be noted that the purchase manufacturers of all raw materials involved in the present invention are not subject to any special restrictions, and exemplary examples include: tannic acid has a CAS number of 1401-55-4, hydroxy-polyethylene glycol-chloride has a product number of 80030216, chloroethyl acrylate has a CAS number of 2206-89-5, rosin has a product number of 13081216254, maleic anhydride has a CAS number of 108-31-6, benzoyl peroxide (peroxide initiator) has a CAS number of 94-36-0, 3-aminopropyltriethoxysilane has a CAS number of 919-30-2, and lysine has a CAS number of 56-87-1; the ball milling medium is a silicon nitride ball with a diameter of 5 mm.

[0031] The preparation method of the polymer is as follows: (1) adding 1 part of tannic acid, 0.35 parts of hydroxy-polyethylene glycol-chloride, 0.4 parts of chloroethyl acrylate, and 0.1 parts of triethylamine to a reaction system; stirring at 100° C. for 20 minutes, adding 2.5 parts of a 5 mol / L NaOH aqueous solution dropwise for 20 minutes; reacting for 5 hours, cooling to room temperature, purifying, and drying to obtain modified tannic acid; (2) under nitrogen protection, heating 1.5 parts of rosin to 125° C., adding 0.3 parts of maleic anhydride and 0.01 parts of a peroxide initiator and mixing evenly, then heating to 190° C., reacting for 4 hours, adding 0.2 parts of modified tannic acid, heating to 280° C., continuing to react for 6 hours, until the temperature drops to 110° C., adding 0.005 parts of an antioxidant 1010, mixing evenly, and cooling to room temperature to obtain a polymer; wherein the molecular weight of the polyethylene glycol is 600.

[0032] Embodiment 1:

[0033] Step 1: Mix silicon nitride powder and ball milling media, and grind them for 4 hours to obtain slurry powder; wherein the ball loading is 40%, the material loading is 40%, and the ball milling is performed at 25r / min;

[0034] Step 2: (1) adding 25 parts of slurry powder to 70 parts of organic glue to obtain a mixed slurry; (2) subjecting the mixed slurry to a sol treatment in a mixer at 50° C. for 4 hours to obtain a mixed slurry A; (3) subjecting the mixed slurry A to a sol ball milling treatment for 6 hours, and filtering through 200 mesh to obtain a high thermal conductivity silicon nitride slurry;

[0035] During the sol ball milling process, the ball loading of the ball milling medium is 40%, the loading amount of the mixed slurry is 40%, and the noise decibel value during the process is 78; the organic colloid includes the following raw materials: by weight, 2 parts of polymer, 1 part of auxiliary agent, and 65 parts of deionized water; the auxiliary agent includes 3-aminopropyltriethoxysilane and lysine in a mass ratio of 3.2:1.5.

[0036] Example 2 is based on Example 1, and the sol ball milling time is 8 hours;

[0037] Step 1: Mix silicon nitride powder and ball milling media, and grind them for 4 hours to obtain slurry powder; wherein the ball loading is 40%, the material loading is 40%, and the ball milling is performed at 25r / min;

[0038] Step 2: (1) adding 25 parts of slurry powder to 70 parts of organic glue to obtain a mixed slurry; (2) subjecting the mixed slurry to a sol treatment in a mixer at 50° C. for 5 hours to obtain a mixed slurry A; (3) subjecting the mixed slurry A to a sol ball milling treatment for 8 hours, and filtering through 200 mesh to obtain a high thermal conductivity silicon nitride slurry;

[0039] During the sol ball milling process, the ball loading of the ball milling medium is 40%, the loading amount of the mixed slurry is 40%, and the noise decibel value during the process is 78; the organic colloid includes the following raw materials: by weight, 2 parts of polymer, 1 part of auxiliary agent, and 65 parts of deionized water; the auxiliary agent includes 3-aminopropyltriethoxysilane and lysine in a mass ratio of 3.2:1.5.

[0040] Example 3 is based on Example 2, and the ball milling speed is 30r / min;

[0041] Step 1: (1) mixing silicon nitride powder and ball milling media, and dispersing and grinding for 4 hours to obtain slurry powder; wherein the ball loading is 40%, the material loading is 40%, and the ball milling is performed at 30 r / min;

[0042] Step 2: (1) adding 25 parts of slurry powder to 70 parts of organic glue to obtain a mixed slurry; (2) subjecting the mixed slurry to a sol treatment in a mixer at 50° C. for 6 hours to obtain a mixed slurry A; (3) subjecting the mixed slurry A to a sol ball milling treatment for 8 hours, and filtering through 200 mesh to obtain a high thermal conductivity silicon nitride slurry;

[0043] During the sol ball milling process, the ball loading of the ball milling medium is 40%, the loading amount of the mixed slurry is 40%, and the noise decibel value during the process is 78; the organic colloid includes the following raw materials: by weight, 2 parts of polymer, 1 part of auxiliary agent, and 65 parts of deionized water; the auxiliary agent includes 3-aminopropyltriethoxysilane and lysine in a mass ratio of 3.2:1.5.

[0044] Comparative Example 1 is based on Example 2, and the ball milling speed is 35 r / min;

[0045] Step 1: Mix silicon nitride powder and ball milling media, and grind them for 4 hours to obtain slurry powder; wherein the ball loading is 40%, the material loading is 40%, and the ball milling is performed at 35r / min;

[0046] Step 2: (1) adding 25 parts of slurry powder to 70 parts of organic glue to obtain a mixed slurry; (2) subjecting the mixed slurry to a sol treatment in a mixer at 50° C. for 5 hours to obtain a mixed slurry A; (3) subjecting the mixed slurry A to a sol ball milling treatment for 8 hours, and filtering through 200 mesh to obtain a high thermal conductivity silicon nitride slurry;

[0047] During the sol ball milling process, the ball loading of the ball milling medium is 40%, the loading amount of the mixed slurry is 40%, and the noise decibel value during the process is 78; the organic colloid includes the following raw materials: by weight, 2 parts of polymer, 1 part of auxiliary agent, and 65 parts of deionized water; the auxiliary agent includes 3-aminopropyltriethoxysilane and lysine in a mass ratio of 3.2:1.5.

[0048] Comparative Example 2 is based on Example 2, and the ball milling speed is 20 r / min;

[0049] Step 1: Mix silicon nitride powder and ball milling media, and grind them for 4 hours to obtain slurry powder; wherein the ball loading is 40%, the material loading is 40%, and the ball milling is performed at 20r / min;

[0050] Step 2: (1) adding 25 parts of slurry powder to 70 parts of organic glue to obtain a mixed slurry; (2) subjecting the mixed slurry to a sol treatment in a mixer at 50° C. for 5 hours to obtain a mixed slurry A; (3) subjecting the mixed slurry A to a sol ball milling treatment for 8 hours, and filtering through 200 mesh to obtain a high thermal conductivity silicon nitride slurry;

[0051] During the sol ball milling process, the ball loading of the ball milling medium is 40%, the loading amount of the mixed slurry is 40%, and the noise decibel value during the process is 78; the organic colloid includes the following raw materials: by weight, 2 parts of polymer, 1 part of auxiliary agent, and 65 parts of deionized water; the auxiliary agent includes 3-aminopropyltriethoxysilane and lysine in a mass ratio of 3.2:1.5.

[0052] Comparative Example 3 is based on Example 2, with a loading of 25%;

[0053] Step 1: Mix silicon nitride powder and ball milling media, and grind them for 4 hours to obtain slurry powder; wherein the ball loading is 40%, the material loading is 25%, and the ball milling is performed at 25r / min;

[0054] Step 2: (1) adding 25 parts of slurry powder to 70 parts of organic glue to obtain a mixed slurry; (2) subjecting the mixed slurry to a sol treatment in a mixer at 50° C. for 6 hours to obtain a mixed slurry A; (3) subjecting the mixed slurry A to a sol ball milling treatment for 8 hours, and filtering through 200 mesh to obtain a high thermal conductivity silicon nitride slurry;

[0055] During the sol ball milling process, the ball loading of the ball milling medium is 40%, the loading amount of the mixed slurry is 25%, and the noise decibel value during the process is 78; the organic colloid includes the following raw materials: by weight, 2 parts of polymer, 1 part of auxiliary agent, and 65 parts of deionized water; the auxiliary agent includes 3-aminopropyltriethoxysilane and lysine in a mass ratio of 3.2:1.5.

[0056] Comparative Example 4 is based on Example 2, with a loading of 50%;

[0057] Step 1: Mix silicon nitride powder and ball milling media, and grind them for 4 hours to obtain slurry powder; wherein the ball loading is 40%, the material loading is 50%, and the ball milling is performed at 25r / min;

[0058] Step 2: (1) adding 25 parts of slurry powder to 70 parts of organic glue to obtain a mixed slurry; (2) subjecting the mixed slurry to a sol treatment in a mixer at 50° C. for 6 hours to obtain a mixed slurry A; (3) subjecting the mixed slurry A to a sol ball milling treatment for 8 hours, and filtering through 200 mesh to obtain a high thermal conductivity silicon nitride slurry;

[0059] During the sol ball milling process, the ball loading of the ball milling medium is 40%, the loading amount of the mixed slurry is 50%, and the noise decibel value during the process is 78; the organic colloid includes the following raw materials: by weight, 2 parts of polymer, 1 part of auxiliary agent, and 65 parts of deionized water; the auxiliary agent includes 3-aminopropyltriethoxysilane and lysine in a mass ratio of 3.2:1.5.

[0060] Comparative Example 5 is based on Example 2, but the ball loading is 25%;

[0061] Step 1: Mix silicon nitride powder and ball milling media, and grind them for 4 hours to obtain slurry powder; wherein the ball loading is 25%, the material loading is 40%, and the ball milling is performed at 25r / min;

[0062] Step 2: (1) adding 25 parts of slurry powder to 70 parts of organic glue to obtain a mixed slurry; (2) subjecting the mixed slurry to a sol treatment in a mixer at 50° C. for 6 hours to obtain a mixed slurry A; (3) subjecting the mixed slurry A to a sol ball milling treatment for 8 hours, and filtering through 200 mesh to obtain a high thermal conductivity silicon nitride slurry;

[0063] During the sol ball milling process, the ball loading of the ball milling medium is 40%, the loading amount of the mixed slurry is 25%, and the noise decibel value during the process is 78; the organic colloid includes the following raw materials: by weight, 2 parts of polymer, 1 part of auxiliary agent, and 65 parts of deionized water; the auxiliary agent includes 3-aminopropyltriethoxysilane and lysine in a mass ratio of 3.2:1.5.

[0064] Comparative Example 6 is based on Example 2, but the ball loading is 50%;

[0065] Step 1: Mix silicon nitride powder and ball milling media, and grind them for 4 hours to obtain slurry powder; wherein the ball loading is 50%, the material loading is 40%, and the ball milling is performed at 25r / min;

[0066] Step 2: (1) adding 25 parts of slurry powder to 70 parts of organic glue to obtain a mixed slurry; (2) subjecting the mixed slurry to a sol treatment in a mixer at 50° C. for 6 hours to obtain a mixed slurry A; (3) subjecting the mixed slurry A to a sol ball milling treatment for 8 hours, and filtering through 200 mesh to obtain a high thermal conductivity silicon nitride slurry;

[0067] During the sol ball milling process, the ball loading of the ball milling medium is 40%, the loading amount of the mixed slurry is 25%, and the noise decibel value during the process is 78; the organic colloid includes the following raw materials: by weight, 2 parts of polymer, 1 part of auxiliary agent, and 65 parts of deionized water; the auxiliary agent includes 3-aminopropyltriethoxysilane and lysine in a mass ratio of 3.2:1.5.

[0068] Comparative Example 7 is based on Example 2, but rosin is not introduced into the modified tannic acid;

[0069] Step 1: Mix silicon nitride powder and ball milling media, and grind them for 4 hours to obtain slurry powder; wherein the ball loading is 40%, the material loading is 40%, and the ball milling is performed at 25r / min;

[0070] The preparation method of the polymer comprises: (1) adding 1 part of tannic acid, 0.35 parts of hydroxy-polyethylene glycol-chloride, 0.4 parts of chloroethyl acrylate, and 0.1 parts of triethylamine to a reaction system; stirring at 100° C. for 20 minutes, and dripping 2.5 parts of a 5 mol / L NaOH aqueous solution for 20 minutes; reacting for 5 hours, cooling to room temperature, purifying, and drying to obtain modified tannic acid; wherein the molecular weight of the polyethylene glycol is 600;

[0071] Step 2: (1) adding 25 parts of slurry powder to 70 parts of organic glue to obtain a mixed slurry; (2) subjecting the mixed slurry to a sol treatment in a mixer at 50° C. for 6 hours to obtain a mixed slurry A; (3) subjecting the mixed slurry A to a sol ball milling treatment for 8 hours, and filtering through 200 mesh to obtain a high thermal conductivity silicon nitride slurry;

[0072] During the sol ball milling process, the ball loading of the ball milling medium is 40%, the loading amount of the mixed slurry is 40%, and the noise decibel value during the process is 78; the organic colloid includes the following raw materials: by weight, 2 parts of modified tannic acid, 1 part of auxiliary agent, and 65 parts of deionized water; the auxiliary agent includes 3-aminopropyltriethoxysilane and lysine in a mass ratio of 3.2:1.5.

[0073] Comparative Example 8 is based on Example 2, but polyethylene glycol is not introduced into tannic acid;

[0074] Step 1: Mix silicon nitride powder and ball milling media, and grind them for 4 hours to obtain slurry powder; wherein the ball loading is 40%, the material loading is 40%, and the ball milling is performed at 25r / min;

[0075] The preparation method of the polymer is as follows: (1) adding 1 part of tannic acid, 0.4 parts of chloroethyl acrylate and 0.1 parts of triethylamine to a reaction system; stirring at 100° C. for 20 minutes, adding 2.5 parts of a 5 mol / L NaOH aqueous solution dropwise for 20 minutes; reacting for 5 hours, cooling to room temperature, purifying and drying to obtain modified tannic acid; (2) under nitrogen protection, heating 1.5 parts of rosin to 125° C., adding 0.3 parts of maleic anhydride and 0.01 parts of a peroxide initiator and mixing evenly, then heating to 190° C., reacting for 4 hours, adding 0.2 parts of modified tannic acid, heating to 280° C., continuing to react for 6 hours, until the temperature drops to 110° C., adding 0.005 parts of an antioxidant 1010, mixing evenly, cooling to room temperature to obtain a polymer;

[0076] Step 2: (1) adding 25 parts of slurry powder to 70 parts of organic glue to obtain a mixed slurry; (2) subjecting the mixed slurry to a sol treatment in a mixer at 50° C. for 6 hours to obtain a mixed slurry A; (3) subjecting the mixed slurry A to a sol ball milling treatment for 8 hours, and filtering through 200 mesh to obtain a high thermal conductivity silicon nitride slurry;

[0077] During the sol ball milling process, the ball loading of the ball milling medium is 40%, the loading amount of the mixed slurry is 40%, and the noise decibel value during the process is 78; the organic colloid includes the following raw materials: by weight, 2 parts of polymer, 1 part of auxiliary agent, and 65 parts of deionized water; the auxiliary agent includes 3-aminopropyltriethoxysilane and lysine in a mass ratio of 3.2:1.5.

[0078] Test 1: When the horizontal ball mill is running, it is impossible to accurately determine the state of the internal balls falling, and it is inconvenient for personnel to adjust the speed of the ball mill. The best ball milling state can be confirmed through noise detection. There are two kinds of sounds during operation, the sound of the balls sliding down and the sound of the balls falling. The sound of the balls falling is the main source of noise.

[0079] The decibel values ​​of Examples 2 to 3 and Comparative Examples 1 to 2 were respectively measured; as shown in Table 1;

[0080] Decibel Value Example 2 77.5 Example 3 78.2 Comparative Example 1 75.9 Comparative Example 2 74.8

[0081] Table 1

[0082] The study found that the larger the noise peak and the louder the ball mill drop sound, the more suitable it is for slurry dispersion grinding.

[0083] Test 2: Determine the quality of the slurry;

[0084] Judgment method: Examples 1 to 3 and Comparative Examples 1 to 8 were subjected to a plate-heating type casting machine scraping test, and the number of surface particles was used as the basis for judgment; rating was given according to the scraping state to judge the quality of the slurry;

[0085] Rating standard: After scraping, the surface particles decrease from more to less, and from appearing to basically eliminating, which meets the requirements; the slurry rating corresponding to the number of particles remaining after grinding is as follows:

[0086] The scraped surface has 0-1 convexity, and the rating is A;

[0087] 2-6 ridges on the scraped surface, rating B;

[0088] The scraped surface has 7-10 convexities, rating C, and the ball milling time is slightly extended;

[0089] The scraped surface has more than 10 protrusions, which is rated D. When the rating is D, the ball milling time needs to be extended;

[0090] After silicon nitride powder is added to the dispersed organic glue system, samples are taken out every h / 2h for the tape casting machine to test the tape casting and scraping test, where the knife height is 120um; the tape casting speed is 0.3m / min, the tape extension is greater than 50cm, and the temperature is 30℃ for 30 minutes; as shown in Table 2;

[0091]

[0092]

[0093] Table 2

[0094] The study found that: Examples 1 to 3 were ball-milled with organic colloid for 6h and 8h, and then filtered through 200 mesh, and were rated A; Table 1 shows that the larger the noise peak and the louder the ball milling sound, the more suitable it is for slurry dispersion and grinding; while the decibel values ​​of Comparative Examples 1 and 2 are not within the range of 77 to 78, and their slurry dispersion is lower than that of the examples. After filtering through 200 mesh, they are rated B.

[0095] The scraping effects of Comparative Examples 3 and 4 do not meet the use requirements; the study found that the loading amount is ≤25%, and the ball-to-material ratio is large, which will increase the useless work loss of the impact friction between the grinding body and the ball mill lining, increase the power consumption, and reduce the output. The particle size D90 of Comparative Example 3 exceeds the requirement by 0.9um, is less than the required value of 1.4um, and the number of particles is small; the loading amount is ≥50%, the ball-to-material ratio is small, and the grinding intensity of the ball on the slurry is insufficient; the grinding and uniformity ability is reduced, the particle size D90 of Comparative Example 4 is 2.2um, which is greater than the required value of 1.4um, and the number of particles is large.

[0096] The effects of Comparative Examples 5 and 6 do not meet the use requirements; because the ball loading is ≤20%, the silicon nitride balls are not enough to form a flow, the energy provided for slurry grinding is low, and the grinding and evenness capacity does not meet the requirements; when the ball loading is ≥50%, the flow trajectory of the silicon nitride balls in the tank is shortened, the efficiency of slurry grinding is reduced, and the grinding and evenness capacity does not meet the requirements.

[0097] Comparative Example 7 is based on Example 2, but rosin is not introduced into the modified tannic acid; the long-chain molecules of the polymer itself are reduced, and the bonding force between the silicon nitride particles is reduced, resulting in a poor scraping effect of the slurry. Comparative Example 8 is based on Example 2, but polyethylene glycol is not introduced into the tannic acid, resulting in a reduced compatibility between the polymer and water, thereby resulting in a poor scraping effect of the slurry.

[0098] Test 3: After adding gentian violet solution to the high thermal conductivity silicon nitride slurry for staining, observe under a microscope and a strong flashlight to see through the slurry. There are no linear uneven stripes, and the viscosity test is uniform and stable; as shown in Table 3;

[0099] Uniformity Viscosity Example 1 No micelle 24608cp Example 2 No micelle 24321cp Example 3 No micelle 24475cp

[0100] Table 3

[0101] Test 4: After adding the silicon nitride powder and organic glue of Example 2, sampling particle size test was performed for the initial h / 2h, and particle size evaluation was performed without ultrasound and with ultrasound for 2 minutes. Anhydrous ethanol was used for dispersion, and the corresponding curves and main values ​​were recorded to determine the particle size level of the slurry.

[0102] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A slurrying process for high thermal conductivity silicon nitride slurry, characterized in that: The steps include: Step 1: Mix silicon nitride powder and ball milling media, and disperse and grind them to obtain slurry powder; Step 2: (1) adding the slurry powder to the organic glue to obtain a mixed slurry; (2) subjecting the mixed slurry to a sol treatment in a blender to obtain a mixed slurry A; (3) subjecting the mixed slurry A to a sol ball milling treatment, and filtering through 200 meshes to obtain a high thermal conductivity silicon nitride slurry; The mixed slurry includes the following raw materials: by weight, 20-30 parts of slurry powder and 70-80 parts of organic glue; the organic glue includes the following raw materials: by weight, 2-3 parts of polymer, 1-1.5 parts of auxiliary agent and 65-72 parts of deionized water; The preparation method of the polymer is as follows: (1) adding tannic acid, hydroxy-polyethylene glycol-chloride, chloroethyl acrylate and triethylamine to a reaction system; stirring at 100°C to 110°C for 20 to 30 minutes, adding a 4 to 5 mol / L NaOH aqueous solution dropwise for 15 to 20 minutes; reacting for 4 to 6 hours, cooling to room temperature, purifying, and drying to obtain modified tannic acid; (2) under nitrogen protection, heating rosin to 120 to 130°C, adding maleic anhydride and peroxide initiator and mixing evenly, then heating to 190 to 200°C, reacting for 3 to 5 hours, adding modified tannic acid, heating to 250 to 280°C, continuing to react for 5 to 7 hours, until the temperature drops to 110 to 125°C, adding antioxidant 1010, mixing evenly, cooling to room temperature, and obtaining a polymer; The auxiliary agent comprises 3-aminopropyltriethoxysilane and lysine in a mass ratio of 3-3.5:1.5-2.

2. The slurrying process of a high thermal conductivity silicon nitride slurry according to claim 1, characterized in that: During the dispersion grinding process, the ball loading of the ball milling medium is 25% to 45%, and the loading of the silicon nitride powder is 30% to 45%; the ball milling speed is 25 r / min to 30 r / min, and the ball milling time is 4 to 8 hours; the noise decibel value during the process is 77 to 78.

3. The slurrying process of a high thermal conductivity silicon nitride slurry according to claim 1, characterized in that: The ball milling medium is a silicon nitride ball; the particle sizes of the slurry powder include 0.1 μm<D10<0.3 μm, 0.5 μm<D50<0.7 μm, and 1.2 μm<D90<1.5 μm.

4. The slurrying process of a high thermal conductivity silicon nitride slurry according to claim 1, characterized in that: The time of the mixer sol treatment is 4 to 6 hours; the viscosity of the mixed slurry A at 50° C. is 24000 cp to 25000 cp.

5. The slurrying process of a high thermal conductivity silicon nitride slurry according to claim 1, characterized in that: During the sol ball milling process, the ball loading of the ball milling medium is 25% to 45%, and the loading of the mixed slurry A is 30% to 45%; the ball milling speed is set based on the noise decibel value in the process being in the range of 77 to 78, and the ball milling time is 6 to 8 hours.

6. The slurrying process of a high thermal conductivity silicon nitride slurry according to claim 1, characterized in that: The raw materials of the modified tannic acid include the following components: by weight, 1 to 1.5 parts of tannic acid, 0.3 to 0.4 parts of hydroxy-polyethylene glycol-chloride, 0.4 to 0.6 parts of chloroethyl acrylate, 0.1 to 0.3 parts of triethylamine, and 2 to 3 parts of 4 to 5 mol / L NaOH aqueous solution; the raw materials of the polymer include the following components: by weight, 1.5 to 3 parts of rosin, 0.3 to 0.5 parts of maleic anhydride, 0.008 to 0.024 parts of peroxide initiator, 0.2 to 0.24 parts of modified tannic acid, and 0.004 to 0.007 parts of antioxidant 1010.

7. Silicon nitride slurry is prepared according to the slurrying process of a high thermal conductivity silicon nitride slurry according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Environment-friendly method for preparing silicon nitride ceramic green body by gel injection molding

    CN108298992A